1987
DOI: 10.1139/y87-233
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dipyridamole on the initiation phase of postischemic acute renal failure in rats

Abstract: Several previous observations support the hypothesis that increased adenosine production and release mediate, at least in part, the reductions in renal blood flow and glomerular filtration rate in ischemic acute renal failure (ARF). If this hypothesis is correct, dipyridamole should potentiate these changes, since it blocks cellular adenosine uptake, thereby increasing the concentration and potentiating the effects of extracellular adenosine. Moreover, theophylline should block the effects of dipyridamole, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 16 publications
4
40
0
Order By: Relevance
“…Animals were pretreated with theophylline or it was given at day 5 after the renal ischemic/hypoxemic event as outlined in the following. Pretreatment with a single dose of theophylline in rats attenuated the reduction in renal blood flow and GFR observed during the initiation phase of postischemic ARF as determined ϳ1 h after releasing a 30-or 45-min occlusion of the renal artery (197). Similar results with theophylline were obtained in the rabbit (100).…”
Section: B Ischemia-reperfusion Injurysupporting
confidence: 70%
See 1 more Smart Citation
“…Animals were pretreated with theophylline or it was given at day 5 after the renal ischemic/hypoxemic event as outlined in the following. Pretreatment with a single dose of theophylline in rats attenuated the reduction in renal blood flow and GFR observed during the initiation phase of postischemic ARF as determined ϳ1 h after releasing a 30-or 45-min occlusion of the renal artery (197). Similar results with theophylline were obtained in the rabbit (100).…”
Section: B Ischemia-reperfusion Injurysupporting
confidence: 70%
“…With regard to studies in humans, a single dose of theophylline, given early after birth, has beneficial effects in reducing the renal involvement and fall in GFR in asphyxiated full-term infants as determined over the first 5 days (14). In contrast, pretreating rats before renal artery occlusion for 30 min with dipyridamole, which increases extracellular adenosine concentrations, intensified the fall in renal blood flow and GFR determined ϳ1 h after releasing the clamp, and this impairment was blocked by theophylline (198). In summary, these data suggest that pretreatment with theophylline can exert beneficial effects in the initiation and maintenance phase of ischemia-reperfusion injury.…”
Section: B Ischemia-reperfusion Injurymentioning
confidence: 97%
“…This work was expanded by Bowmer et al (1986) who ameliorated a glycerol-induced acute renal failure by the more specific adenosine receptor antagonist 8-phenyltheophylline, an agent that, in addition, is thought to have no inhibitory effects on phosphodiesterase. Lin et al (1987) showed that theophylline increased both GFR and renal blood flow during the initiation phase of post-ischaemic acute renal failure in rats. More recently the same authors (Lin et al, 1988), in addition to their previous work, investigated the effect of theophylline during the maintenance phase of post-ischaemic acute renal failure in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that ENT inhibition with dipyridamole is associated with an initial constriction of the afferent and efferent arterioles at an early phase and subsequent dilation at a later phase, with the same degree of vasoconstrictive and vasodilatory effect on both arterioles in rats (62). In contrast to these studies, previous studies report vasoconstrictive properties of dipyridamole during the initiation phase of postischemic acute renal failure in rats (63) or in patients with liver cirrhosis (64). Thus, we were somewhat surprised that the present findings implicate a biochemical crosstalk…”
Section: Discussionmentioning
confidence: 79%